Substantiation of the development variant of freight forwarding company under uncertainty conditions - Gladkovska, Valentyna (Technology audit and production reserves, 2017)
The object of research is justification of the development of a freight forwarding company under uncertainty conditions. The main factors of uncertainty in the development of freight forwarding companies have been identified and characterized. The main factors of uncertainty in making decisions on the development of a freight forwarding company are potential volumes of cargo for servicing, which are formed under the influence of a competitive environment, volumes of foreign trade cargo and the state of the transport system. The transformation of the uncertainty of information about the state of the market as a function of time is analyzed. It is characterized how the structure of information in terms of its degree of uncertainty changes as the planning horizon of development activities decreases and the moment of their realization comes. Experimental calculations for the choice of the development of a complex of services of a freight forwarding company are developed and presented. For the selection procedure, an adaptation of a well-known method is suggested that takes into account the multicriteria choice, which corresponds to the actual needs of practice under uncertainty conditions. This method in the form of a combination of operations on fuzzy sets and Saaty pairwise comparison method is adapted to choose the direction of development of transport forwarding services by using a set of relevant criteria. This extends the boundaries of using the known method. The proposed method will allow the freight forwarding company to determine the most appropriate development option, taking into account the system of criteria. The results of calculations from four variants of development have shown that the third and fourth development options have the greatest advantage, which obtained a maximum value of 0.70 and 0.68 with an insignificant difference. They received priority over the first and second development options, which make it the final choice when making a decision.